SELF ESTEEM REMAJA PENGGUNA INSTAGRAM DITINJAU DARI BODY IMAGE DAN SOCIAL COMPARISON SEBAGAI MODERATOR - Kato, Sherly Yuriko; Virlia, Stefani (Jurnal Psikologi, 2024)
Instagram is a visual-based platform that is popular among teenagers. Beauty standards on Instagram have an impact on users' body image. Dissatisfaction with body image causes individuals to make social comparisons which can reduce self-esteem. The higher the level of comparison, the greater the impact of body image on self-esteem. This study aims to determine the influence of social comparison, body image, and self-esteem variables. This research uses a quantitative approach and a cross-sectional correlational design. The population of this study was 155 with the characteristics of active Instagram users, aged 12-19 years, and domiciled in Surabaya, using convenience sampling data collection techniques. Findings reveal that body image influences adolescents' self-esteem (F = 48.576  p < .001). However, social comparison has no effect in moderating body image on increasing or decreasing self-esteem. Research findings show that Instagram is a platform for adolescents to seek feedback and shape their body image through social comparison with existing content, thus influencing individual self-esteem.